2021
DOI: 10.3390/diagnostics11122308
|View full text |Cite
|
Sign up to set email alerts
|

Association between Altered Oncogenic Signaling Pathways and Overall Survival of Patients with Metastatic Colorectal Cancer

Abstract: Systemic characterization of genomic alterations into signaling pathways helps to understand the molecular pathogenies of colorectal cancer; however, their clinical implications remain unclear. Here, 128 patients with metastatic colorectal cancer (mCRC) receiving targeted next generation sequencing were retrospectively enrolled to analyze the impact of altered oncogenic pathways on clinical outcome. The datasets from Memorial Sloan Kettering Cancer Center were used for validation. In 123 patients with non-MSI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The TGF-β signaling pathway regulates tissue development and homeostasis, and genomic alterations in this signaling pathway are involved in CRC progression ( 36 , 37 ). Genomic TGF-β pathway alterations have been identified in 30% of rectosigmoid junction or rectum cancer patients and only 12% of in sigmoid colon cancer patients ( 38 ). Research using The Cancer Genome Atlas (TCGA) and Memorial Sloan Kettering Cancer Center data sets have shown that alterations in the TGF-β pathway are correlated with worse overall survival in patients with metastatic CRC ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β signaling pathway regulates tissue development and homeostasis, and genomic alterations in this signaling pathway are involved in CRC progression ( 36 , 37 ). Genomic TGF-β pathway alterations have been identified in 30% of rectosigmoid junction or rectum cancer patients and only 12% of in sigmoid colon cancer patients ( 38 ). Research using The Cancer Genome Atlas (TCGA) and Memorial Sloan Kettering Cancer Center data sets have shown that alterations in the TGF-β pathway are correlated with worse overall survival in patients with metastatic CRC ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the RTK-RAS pathway is related to the pathogenesis of CRC ( 22 ) and mutations in the RTK-RAS pathway led to decreased relapse free survival (RFS) in CRC patients ( 23 ). The Cancer Genome Atlas Pan-Cancer Analysis Project examined 123 patients with non-MSI, highly metastatic CRC, and found significant changes in the RTK-RAS, Notch, Wnt, p53, PI3K, TGF-β, and Myc pathways ( 24 ). These changes in the RTK-RAS and Notch pathway have been shown to be strongly related to poor OS in patients whose colorectal liver metastases were resected ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In CRC, SMAD4 is one of the most frequently mutated genes based on a series of high-throughput analyses. A recent study utilizing next-generation sequencing (NGS) including 123 non-MSI-high mCRC patients demonstrated an about 20% mutation occurrence of SMAD4 [37]. TGFBR2 mutations are also often shown in CRC [38].…”
Section: Role Of Tgf-β Signaling In the Carcinogenesis And Progressio...mentioning
confidence: 99%